Geochemistry, stable isotopes and fluid inclusion studies of the Otjikoto gold deposit, Central Namibia - Negonga, Lisias (Department of Geological Sciences, 2019)
The Otjikoto gold deposit is located within the Damara Orogenic Belt which is part of the system of Pan-African mobile belts. The Damara Belt is a northwest trending orogenic belt which formed through sequences of spreading, rifting, subduction and from continental collision between the Congo, Kalahari and Rio Delta Plata Cratons between 900 Ma and 450 Ma. Mineralisation at Otjikoto is hosted by a group of metamorphic rocks which consist of biotite schists from the Okonguarri Formation, albitites from the Oberwasser member and marble units from the Okawayo member. The gold mineralization occurs in a sheeted vein network system with veins which are positioned parallel towards the foliation of the albitites and hornfels of the Oberwasser Member. The vein types include both quartz and carbonate hosted vein types. The vein mineralogy includes magnetite, pyrite and pyrrhotite which are associated with amphibole, quartz, almandine garnets, and free gold. A fluid inclusion study carried out on the vein quartz showed the co-existence of the aqueous, carbonic and aqueouscarbonic fluid inclusions within the Okonguarri Formation. The aqueous inclusions have moderate to high salinities with salinities ranging from 30.0 to 44.5 wt. % NaCl eq. in aqueous inclusions with halite crystals and from 0.9 to 22.9 wt. % NaCl eq. in inclusions without halite crystals. The total homogenisation temperatures, Th tot (L), ranged from 151 to 488 °C in the aqueous-carbonic inclusions and from 156 to 444 °C in the aqueous inclusions. The melting temperature of CO2 (TmCO2) ranged from -60.3 to -57.5 °C in carbonic inclusions and from - 60.2 to -57.2 °C in aqueous-carbonic inclusions. It is proposed that the aqueous and carbonic inclusions (CO2-CH4) from the Okonguarri Formation are the end members of fluid immiscibility. The presence of CO2 and CH4 is indicated by the low TmCO2 values and may be justified by the decomposition of the carbonaceous metasediments which are found in the stratigraphy at Otjikoto. The δ 18O values range from of 8.35 ‰ to 8.75 ‰ for the magnetite and 17.51 ‰ to 18.47 ‰ for the vein quartz samples. Analysis of the microprobe data on the amphiboles shows that the analysed grains are made up of anthophyllites. Microprobe data of the chlorites showed that the majority of the chlorites are made up of ripidolites. Temperatures of chlorite formation were calculated to be in the range of 221°C to 358 °C by using chlorite geothermometric equations. Major element variation diagrams show a strong negative correlation of TiO2, Al2O3, MgO, Na2O and FeOt vs SiO2. Variation diagrams were also plotted for the trace elements vs Zr. The Sr, Y, La and Ce vs Zr plots show a strong positive correlation.